2016
DOI: 10.1590/1982-0224-20150189
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anesthetic, tag size, and surgeon experience on postsurgical recovering after implantation of electronic tags in a neotropical fish: Prochilodus lineatus (Valenciennes, 1837) (Characiformes: Prochilodontidae)

Abstract: Implantation of telemetry transmitters in fish can be affected by different parameters. This study aimed to evaluate the effect of type of anesthetic, tag size, and surgeon experience on surgical and postsurgical wound healing in the neotropical fish Prochilodus lineatus. In total, eighty fish were surgically implanted with telemetry transmitters and forty fish were kept as controls. Forty fish were implanted with a small tag and other forty were implanted with a large tag. Similarly, forty fish were anestheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 55 publications
0
12
0
1
Order By: Relevance
“…The sterile procedures followed the protocol outlined by Lopes, Alves, Silva, Bedore, and Pompeu (2016). While on the tagging plat- …”
Section: Hydrological and Physicochemical Variablesmentioning
confidence: 99%
“…The sterile procedures followed the protocol outlined by Lopes, Alves, Silva, Bedore, and Pompeu (2016). While on the tagging plat- …”
Section: Hydrological and Physicochemical Variablesmentioning
confidence: 99%
“…External healing rate at the surgical site following tag implantation has been extensively studied in a variety of fish species. These studies have revealed that there are several factors which influence healing rate such as fish species, age, environment, water temperature, tag size, and suture type (Collins et al, 2013, Lopes et al, 2016, Rozynski et al, 2017, Schoonyan et al, 2017). In the current study, the presence of the acoustic tag did not appear to influence external healing when compared to individuals who received the sham surgery alone.…”
Section: Healing Rate and Tag Encapsulationmentioning
confidence: 99%
“…Voucher specimens were deposited at Lavras Federal University Ictiological Collection (CI-UFLA09989991000). The tagging protocol used was the one outlined by Lopes et al (2016). Individuals selected for tagging were transferred to an aerated tank with eugenol (0.05 mg/L).…”
Section: Methodsmentioning
confidence: 99%
“…If the gonad could not be visualized, the sex of the fish was classified as indeterminate. After the tagging procedure, fish were placed in a net pen in the river until fully recovered from surgery (sensu Lopes et al, 2016) and then released at the location of capture.…”
Section: Methodsmentioning
confidence: 99%